Structural renovation of blocks in build-up area of Jiangnan cities, taking Suzhou new district as an example - Fang Zhang; Xi Zhou (iScience, 2023)
Summary: The rationality of block scale and structure is the guarantee of vitality and humanization quality, facing complex and diverse problems, and the structure reconstruction of urban built-up areas is one of the most difficult challenges in the process of promoting the block system. The traditional planning-construction strategy, as practice in recent years has demonstrated, faces challenges in terms of construction costs, demolition costs, property rights, and jurisprudence. Based on the interaction of the block structure and external space, the study presents a “implant-reconstruction” model. It investigates possibilities of implanting elements and graphically depicts the potential impact of implant-reconstruction using Space Syntax. The findings indicate that the external space implantation mode may actively encourage the construction of small-scale blocks and has benefits in terms of texture respect, low impact, and ease of operation. The simulation and pre-judgment dynamically illustrate the viable path and gives a scientific reference for block alteration.